Asset prices and monetary policy : four views - Gertler, Mark.; Centre for Economic Policy Research (Great Britain); Bank for International Settlements (London : Centre for Economic Policy Research (CEPR) ; Basle : Bank for International Settlements, 1998)
This report collects the views of several prominent scholars and central bankers on whether and how asset price developments can be incorporated in the design of monetary policy. These views were expressed in a concluding panel discussion of a conference on Asset Prices and Monetary Policy organized by CEPR and the BIS.
On 26 and 27 January 1998 the BIS and CEPR organized a conference on the subject of this book. ... This volume collects the views expressed by the participants in the panel discussion that concluded the conference." -- Foreword.
Includes bibliographical references (p. 27).
oif 07/08/15
Loan
Keywords: Monetary policy -- Congresses. Securities -- Prices -- Congresses; Banks and banking, Central; Stocks -- Prices